Deciphering charge-storage mechanisms in 3D MnOx@carbon electrode nanoarchitectures for rechargeable zinc-ion cells. (29th January 2019) - Ko, Jesse S.; Donakowski, Martin D.; Sassin, Megan B.; Parker, Joseph F.; Rolison, Debra R.; Long, Jeffrey W.
Abstract: Abstract : We previously demonstrated that electrode architectures comprising nanoscale birnessite-like MnO x affixed to three-dimensional carbon nanofoam (CNF) scaffolds offer performance advantages when used as cathodes in rechargeable zinc-ion cells. To discern chemical and physical changes at the MnO x @CNF electrode upon deep charge/discharge in aqueous Zn 2+ -containing electrolytes, we deploy electroanalytical methods and ex situ characterization by microscopy, elemental analysis, x-ray photoelectron spectroscopy, x-ray diffraction, and x-ray pair distribution function analyses. Our findings verify that redox processes at the MnO x are accompanied by reversible precipitation/dissolution of crystalline zinc hydroxide sulfate (Zn4 (OH)6 (SO4 )· x H2 O), mediated by the more uniformly reactive electrode structure inherent to the CNF scaffold.